Cortisol/cortisone ration: A predicative marker of overtraining? - Gouarne, C.; Groussard, C.; Delamarche, P.; Gratas-Delamarche, A.; Duclos, M. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Monitoring cortisol responses to training has been suggested to be useful in diagnosing the overtraining syndrome, but there are large discrepancies between studies. Recently, it has become apparent that tissue-specific enzyme (11Beta-hydroxysteroid dehydrogenase (11Beta-HSD)) exerts an important level of control of cortisol action at the tissue level (3). Two isoenzymes of 11 Beta-HSD interconvert hormonally-active cortisol and inactive cortisone within target cells. Understanding the function of 11Beta-HSD in a trained population provides another insight into cortisol action in adaptation or maladaptation to training. Methods Nine untrained men (UT) and 10 endurance-trained men (triathletes) were following during the season 2002-2003 and they visited to the laboratory three times: in November 2002, in March and June 2003. In November, triathletes resumed training for 1 month after the end of the season and training load was low. In March high intensity and volume training were performed and in June volume training decreased and specific training was privileged. During each test visit we measured excretion of cortisol and cortisone in overnight urine (urinary cortisol/cortisone ratio is a good index of the 11Beta-HSD activity), total score of fatigue (1), total training load (2), and their performances and their feelings during the competition period. In the triathletes group, 2 individuals developed an overtraining syndrome during the season (OT1 and OT2). They were thus removed from the triathletes group and evaluated individually. Results In March and June, OT1 and OT2 showed a high score of fatigue with sleeping disorders and general stress. Additionally, in March OT men presented a very high training load level compared to the triathletes group. During the competition period (July to September), they suffered of a decline in their performances and of a psychological saturation, and had to reduce the training and the competition. Urinary cortisol and cortisone of the UT and triathletes group decreased from November to June with no difference between the two groups. In the same way, urinary cortisol and cortisone concentrations of the OT men were comparable to the mean values of the triathletes and UT group. Overnight Cortisol/cortisone ratio was stable in November, March and June, both in the UT and in the triathletes group. By contrast, OT men ratios showed a different pattern. In November and June overnight urinary cortisol/cortisone ratios of OT were identical to those of the UT and triathletes group. On the contrary, in March, (high total training load period) OT men showed a large increase of cortisol/cortisone ratios (fig 1) Discussion/Conclusion This study reveals that a large increase of overnight urinary ratio could be a predicative marker of the overtraining syndrome. Nevertheless, this result has to be confirmed in a larger population. Urinary cortisol/cortisone measurement is very practical and non-stressful for the athletes. It should be measured regularly during the season with particular attention during the high load period of training. Atlaoui et al. showed that cortisol/cortisone ratio (in 24-h urinary) was positively related to the training load in a population of swimmers. During the day, the anti-inflammatory action of cortisol is beneficial for the athletes and the increase of cortisol/cortisone ratio could be a marker of a good adaptation of the athletes to high training load. On the contrary, during the night, a cortisol-induced muscle catabolic process is deleterious for the athletes, and the inactivation of cortisol into cortisone could protect the cortisol target tissues against the effects of the exercise-induced hypercortisolism. Low inactivation of cortisol into cortisone (cortisol/cortisone >1) in overtrained triathletes suggested an inhibition of 11Beta-HSD2 and consequently of the tissue protective mechanisms against endogenous prolonged hypercortisolism. This study confirms the importance of longitudinal clinical and endocrinal evaluation in the highly trained athletes population.